Acceptance of exoskeletons and attribution of control - Theisen, Maximilian; Löloff, Johanna; Mertens, Alica; Funke, Joachim (Open Science Framework, 2022)
Correlational analyses of acceptance of smart mobility devices (exosuit and exoskeleton) and attributions of gain and loss of control.
Gesehen am 26.02.2026